A Stylistic Analysis of Chinua Achebe’s Things Fall Apart - Melly Kosasih, Marcella (International Journal of English Literature and Social Sciences (IJELS), 2019)
The present research aims to analyze the writing style of Chinua Achebe in his novel Things Fall Apart. The focus of this research is a stylistic analysis of figures of speech, as classified by Leech and Short as one of stylistic categories, in connection with the author’s purpose of delivering his message to the readers. The findings of the research confirmed that some figures of speech, such as metaphor, simile, personification, and onomatopoeia, are foregrounded by the author to convey meaning and heighten effect so that they helped transmit the author’s purpose. They were used to describe the characterization of the protagonist, the description of the white men as the antagonist, the description of the Igbo’s traditions, and the description of the setting of place. Chinua Achebe has successfully made use of the figures of speech to clearly describe the unique life of the native Africans.